OP0013 Treatment of Epicondylitis by Ultrasound-Guided Local Injections of Autologous Conditioned Plasma (ACP®): A Double-Blind Placebo-Controlled Randomized Clinical TRIAL with 1-Year Follow-Up. (10th June 2014) - Le Goux, P.; Montalvan, B.; Leparc, J.; Klouche, S.; Hardy, P.; Breban, M.
Abstract : Background: Local injections of corticosteroid represent a standard of care for epicondylitis, albeit it may adversely impair the healing process (1). Recently, local injections of growth factors-containing platelet-rich plasma (PRP) have been proposed as a new therapeutic technique, with the aim of boosting tendon repair (2). Ultrasound guidance of intra-tendinous injections seems to optimize the technical procedure (3). Objectives: The main objective was to assess the efficacy of two local injections of PRP to treat epicondylitis of recent evolution. Methods: A prospective double-blind placebo-controlled randomized trial was conducted during 2011-2012. Inclusion criteria were recent epicondylitis (pain≤3 months), confirmed by MRI and/or ultrasound and written informed consent. Exclusion criterion was previous corticosteroid infiltration. Two ultrasound-guided injections were performed at 4 weeks interval of either PRP (ACP®, Arthrex) or saline solution. Patients were monitored by an independent clinical evaluator blinded to the treatment at baseline, 1, 3, 6 and 12 months follow-up. The primary evaluation criterion was the relative improvement from baseline to 6 months in pain score (PS) on visual analog scale (0-10). Secondary criteria were the assessment of pain (yes/no) on isometric contraction of the second radial and of the extensor digitorum communis, the Roles-Maudsley score (1 to 4), the proportion of asymptomatic patients (PS ≤1) at 6 and 12 months follow-up and the proportion of patients with persistent pain (PS>2) at 12 months follow-up. Based on a sample size calculation, 21 patients in each group were needed. Results: Fifty patients were included, 25 in each group, 34 men/16 women, mean age 47±9.2 years in the ACP group and 46.4±8.6 years in the control group. Six patients dropped out of the study between baseline and 6 months, 3 in each arm. At 6-month follow-up, no statistically significant difference was found between groups for mean relative improvement in pain (ACP: -63.2±22.4%, control: -69.7±25.1%, p=0.24). No statistically significant difference was found for the secondary criteria. In the two groups, the pain score decreased significantly between two consecutive visits from 6.8±0.8 (PRP) and 7±1 (control) at baseline to 2.5±1.6 (PRP) and 2.1±1.6 (control) at 6 months and 1.65±1.5 (PRP) and 1.8±2.1 (control) at 12 months. At 6-month, 34% of all patients were asymptomatic and 66% at 1-year. The proportion of patients with persistent pain at 12 months was 23.8% in both groups. No adverse-effect was observed. Conclusions: The therapeutic effect of two ultrasound-guided ACP injections for epicondylitis of recent evolution (≤3 months) was not significantly superior to injections of saline, in a prospective randomized double-blind study with 12-months follow-up. The similarly favorable outcome registered in both study groups, may be linked to a stimulating role of ultrasound-guided intra-tendinous injections ("prolotherapy") on the process of tendon repair. References: Coombes BK et al., JAMA 2013 6; 309(5):461-9 Peerbooms JC et al., Am J Sports Med 2010;38(2):255-62 Chiavaras MM, Jacobson JA, Semin Musculoskelet Radiol 2013;17(1):85-90 Disclosure of Interest: P. Le Goux: None declared, B. Montalvan: None declared, J. Leparc: None declared, S. Klouche: None declared, P. Hardy Grant/research support: Arthrex, M. Breban: None declared DOI: 10.1136/annrheumdis-2014-eular.2480